Effectiveness Of Lactation Massage And Oxytocin Massage On ASI Production In PMB Hasna Dewi Kota Pekanbaru - Karlinah, Nelly; Irianti, Berliana (Poltekkes Kemenkes Riau Under Health Ministry Republik Indonesia, 2023)
Breast milk (ASI) is very important for babies, successful exclusive breastfeeding can be achieved if the mother's breast milk is sufficient for the baby's needs. The phenomenon in the field is that newborn babies are often given formula milk on the grounds that little milk comes out. Women are physiologically capable of producing sufficient breast milk. However, sometimes there are problems with breastfeeding, one of which is the mother's breast milk production is not smooth and the output is small. The aim of this research was to determine the effectiveness of lactation massage and oxytocin massage on breast milk production. Types of researchPre experimental with a plantwo group pretest posttest designs. This research will be carried out at Hasna Dewi's Independent Midwife Practice (PMB) Pekanbaru City in June-November 2023, with a sample size of 15 for oxytocin massage, 15 for lactation massage. It is hoped that this research will be useful, especially for postpartum mothers, in increasing production. breast milk. Bivariate results using tests Wilcoxon Rank Test, the effectiveness of lactation massage on breast milk production obtained a p value of 0.005 (p < 0.05) and the effectiveness of oxytocin massage on breast milk production obtained a p value of 0.008 (p < 0.05). So it can be concluded that there is an influence of lactation massage and oxytocin massage on breast milk production. It is hoped that this research will be an alternative to increase breast milk production in postpartum mothers